Microstructure and refinement mechanism of Al–5Ti–1B alloys - LI Yang; GUO Xu-qiang; XU Lei; LI Chang-yun; LIU Xiao-fei (Fenmo yejin jishu)
Two kinds of Al–5Ti–1B alloys were prepared by powder mixing + hot extrusion and powder mixing + gas atomization + hot extrusion, respectively. The microstructures of the Al–5Ti–1B alloys prepared by two kinds of processes were studied, and the grain refinement properties were assessed. The results show that, the TiB2 particles can be uniformly distributed and the growth of TiAl3 phase can be inhibited by these two kinds of processes. The Al–5Ti–1B alloys with the mass fraction of 0.2% are added to the melt of 7050 aluminum alloys. The grain refinement effect of the Al–5Ti–1B alloys prepared by powder mixing + hot extrusion is not obvious, and the grain size of 7050 aluminum alloys is still up to 1400 μm. The grain refinement effect of the Al–5Ti–1B alloys prepared by powder mixing+ gas atomization + hot extrusion is very good, the average grain size of 7050 aluminum alloys is only 176 μm. According to this experimental phenomenon, a new explanation for the grain refinement and double nucleation mechanism of the Al–Ti–B alloys is proposed.